2022
DOI: 10.1227/neu.0000000000002020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Withdrawal of Life-Sustaining Therapies in Patients With Traumatic Brain Injury: A Retrospective Trauma Quality Improvement Program Database Study

Abstract: Many patients with severe traumatic brain injuries (TBIs) undergo withdrawal of life-sustaining therapies (WLSTs) or transition to comfort measures, but noninjury factors that influence this decision have not been well characterized. We hypothesized that WLST would be associated with institutional and geographic noninjury factors. All patients with a head Abbreviated Injury Scale score ≥3 were identified from 2016 Trauma Quality Improvement Program data. We analyzed factors that might be associated with WLST, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Withdrawal of life supporting treatment is common in severe TBI and has been studied by multiple researchers. 4,15 In our study, severe TBI was found to be an independent predictor of WLST in geriatric trauma patients. It is well known that severe TBI patients have poorer outcomes, and the families may choose WLST in these patients because of the uncertainty of their progress and return to preinjury health.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Withdrawal of life supporting treatment is common in severe TBI and has been studied by multiple researchers. 4,15 In our study, severe TBI was found to be an independent predictor of WLST in geriatric trauma patients. It is well known that severe TBI patients have poorer outcomes, and the families may choose WLST in these patients because of the uncertainty of their progress and return to preinjury health.…”
Section: Discussionsupporting
confidence: 50%
“…Withdrawal of life supporting treatment is common in severe TBI and has been studied by multiple researchers 4,15 . In our study, severe TBI was found to be an independent predictor of WLST in geriatric trauma patients.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…3,4 Withdrawal of life-sustaining treatment (WLST) decisions are complex in this population; providers must often rely on patient factors, including age and premorbid functional status, and injury characteristics, including the extent of neurologic deficit. 5,6 Despite advances in TBI outcome prediction and care pathways, there remains a relative paucity of tools to navigate withdrawal-of-care decision-making and prognostication resulting in variable practice patterns. 7 The harm of premature WLST is potential loss of recovery opportunity; alternatively, continued invasive support in the face of a poor prognosis leads to excess suffering, healthcare system inefficiencies, and potential opportunity costs.…”
mentioning
confidence: 99%
“…Previous groups that have examined WLST in the context of severe TBI have largely focused on associations between patient characteristics, such as insurance status, race, comorbidities, and injury factors, and hospital characteristics. 5,10,11 We postulate that additional unmeasurable attributes pertaining to hospital culture and practice patterns contribute to residual observed practice variability. Estimating the magnitude of this unexplained variation might direct further investigation into these contextual factors to increase adherence to equitable end-of-life care standards.…”
mentioning
confidence: 99%